(untitled) (Journal of International Studies, 2025)
This article examines Vietnam’s strategic approach to managing global dynamics, focusing on organisational adaptation and strategic management amid complex technological, geopolitical, and environmental challenges. Applying complexity theory, landscape genetics, and strategic improvisation, this study provides insights into Vietnam’s responses to geopolitical conflicts, climate change impacts, and cybersecurity threats. It highlights Vietnam’s strategies in environmental conservation, such as combating sea level rise, and the role of technological integration, including artificial intelligence and digital transformation, in enhancing national resilience. Vietnam’s partnerships in maritime security, especially concerning the South China Sea, illustrate its adaptive capabilities in securing territorial and economic interests. Additionally, this paper emphasises the significance of corporate entrepreneurship and talent management in fostering innovation and resilience. The findings underscore the necessity for flexible, collaborative strategies for sustainable development and national security, positioning Vietnam as a resilient actor within the Asia-Pacific region.